Ajuourhållning av ungskogsdata med hjälp av digitala flygbilder - Johansson, Henrik (SLU/Dept. of Forest Resource Management, 2008)
The purpose of this study is to investigate whether it is possible for SCA to update their stand register with use of digital aerial photos photographed with a Zeiss/Intergraph DMC. "Updating" in this study implies the delineation of stands and estimating stand variables such as average stand height, volume density, stand volume, and tree species composition in order to identify stands which can be of current interest for thinning.